Program Unggulan Masjid dalam Peningkatan Keagamaan Bagi Para Muallaf di Masa Pandemi Covid 19 (Studi Kasus di Masjid Nurul Hidayah Desa Cisantana Kec. Cigugur Kuningan) - Khaerul Wahidin; Muhammad Azka Maulana; Aang Subhanudin; Muhammad Irfan (AL-MUFASSIR, 2020)
Begins the discourse this time, we invite all of us to return flash-back or look back at the history of strategic functions than the Mosque. That as a noble place and full of blessings as well as the pride of Muslims especially in the modern era as it is today, it is appropriate in the context of da'wah as well as strengthening aqidah Islamiyah, the function of the Mosque should be put as a center of activity and development of the quality of Muslims. Mosque is not only a place of worship (mahdhoh) such as prayer and other routine personal activities but more than that, the Mosque is supposed to be a strategic place to make people more longing to get closer to God and people also long to visit the Mosque. Therefore, the Mosque or in this case the DKM Board must have bargaining, creativity and innovation. Both in terms of idarotul-mosques, mosques to riayatul-mosques in the form of work programs; The numerator.